Down-regulation of amygdala activation with real-time fMRI neurofeedback in a healthy female sample - Paret, Christian; Kluetsch, Rosemarie; Ruf, Matthias; Demirakca, Traute; Hoesterey, Steffen; Ende, Gabriele; Schmahl, Christian (Frontiers in Behavioral Neuroscience, 2014)
Psychiatric conditions of emotion dysregulation are often characterized by difficulties in regulating the activity of limbic regions such as the amygdala. Real-time functional magnetic resonance imaging (rt-fMRI) allows to feedback brain activation and opens the possibility to establish a neurofeedback (NF) training of amygdala activation, e.g. for subjects suffering from emotion dysregulation. As a first step, we investigated whether feedback of the amygdala response to aversive scenes can improve down-regulation of amygdala activation. One group of healthy female participants received amygdala feedback (N=16) and a control group was presented with feedback from a control region located in the basal ganglia (N(sum)=32). Subjects completed a one-session rt-fMRI-NF training where they viewed aversive pictures and received continuous visual feedback on brain activation (REGULATE condition). In a control condition, subjects were advised to respond naturally to aversive pictures (VIEW), and a neutral condition served as the non-affective control (NEUTRAL). In an adjacent run, subjects were presented with aversive pictures without feedback to test for transfer effects of learning. In a region of interest (ROI) analysis, the VIEW and the REGULATE conditions were contrasted to estimate brain regulation success. The ROI analysis was complemented by an exploratory analysis of activations at the whole brain level. Both groups showed down-regulation of the amygdala response during training. Feedback from the amygdala but not from the control region was associated with down-regulation of the right amygdala in the transfer test. The whole-brain analysis did not detect significant group interactions. Results of the group whole-brain analyses are discussed. We present a proof-of-concept study using rt-fMRI-NF for amygdala down-regulation in the presence of aversive scenes. Results are in line with a potential benefit of neurofeedback training for amygdala regulation.